(untitled) (Research, Society and Development, 2021)
The civil construction segment is a great vector for development, however along it production chain, the civil constriction industry inevitably generates an impact on the environment with the Generation if solid waste. Mitigation would be the management of RCD, reuse or recycling of RCD are pointed out as a solution. In this scenario, the study objective is to evaluate the technical feasibility of using RCD’s from the civil constriction industry in the city of Paragominas/PA. The method adopted was field research as a technical procedure. The study was carried out in 14 districts of the city in which samples of RCD’s were collated, from which specimens were produced and submitted to the compression test. In the results, the percentage found for class A waste corresponds to eighty-seven percent, with twenty-two percent for mortar and twenty-seven percent for concrete and the Other ware with thirty-seven and fifty-four percent. From the compression test, the strengths found in the work were satisfactory for concrete with a non-structural purpose, in addition to which it was clear that reusing the aggregate is a great economic, social and environmental attraction.